Discussion on the optimization of personalized medication using information systems based on pharmacogenomics: an example using colorectal cancer - Yuan, Mengying; Zheng, Yuankun; Wang, Fei; Bai, Niuniu; Zhang, Haoling; Bian, Yuan; Liu, Hao; He, Xia (Frontiers in Pharmacology, 2025)
Pharmacogenomics (PGx) is a powerful tool for clinical optimization of drug efficacy and safety. However, due to many factors affecting drugs in the real world, PGx still accounts for a small proportion of actual clinical application scenarios. Therefore, based on the information software, pharmacists use their professional advantages to integrate PGx into all aspects of pharmaceutical care, which is conducive to promoting the development of personalized medicine. In this paper, the establishment of an information software platform is summarized for the optimization of a personalized medication program based on PGx. Taking colorectal cancers (CRC) as an example, this paper also discusses the role of PGx in different working modes and participation in drug management of CRC patients by pharmacists with the help of information systems. Finally, we summarized the recommendations of different PGx guidelines to provide reference for the follow-up personalized pharmaceutical care.